Convenio internacional para la seguridad de la vida humana en el mar y su implementación en el transporte marítimo internacional (2020)
Maritime transport for its efficient development involves a considerable number of participants, who may be affected by incidents that arise in said activity, which is why the IMO created the convention for the safety of life in order to increase maritime safety. Human at sea, which focuses its efforts on the adoption of standards related to maritime safety, whose amendments and regulations have been modified and adapted as the shipping industry evolves. Based on the above, this work analyzes the new update of said agreement and its implementation in international maritime transport; To comply with what is proposed, the agreement is initially described, its importance is determined and each of the norms that comprise it is detailed; Below are the regulatory changes that have arisen as a result of the update that came into effect from the year 2020 and the relevance of each of these is analyzed, compared to the previous version; Finally, the incidence of these changes in international shipping is determined, and how their application can positively or negatively affect international trade.